Kepuasan Pembelajaran Daring Selama Masa Pandemi Covid-19 Bagi Mahasiswa - Tri Arini (PENA NURSING, 2023)
Background: Learning satisfaction is a positive attitude towards teaching and learning services by educators. Each individual has a different level of satisfaction. Students as academic customers certainly expect maximum satisfaction from every service available at the institution that can support the improvement of science and technology. The phenomenon that is currently sweeping the world, including in Indonesia, namely the Covid-19 pandemi, the government ordered Physical Distancing and Social Distancing which resulted in the learning process being carried out online. Purpose: The purpose of this research was to find out how satisfied students are during online learning. Method: This research method was carried out using a qualitative approach through focus group discussions with 10 students at the Nursing Academy YKY Yogyakarta Data analysis was carried out using content analysis by researchers who had attended qualitative research training. Trushwortiness is carried out by peer debreafing with other lecturers who have often become peer debreafing qualitative research teams. Results: The research there are four themes, namely: The perceived quality of learning has not been fully felt; The perceptions that students get in online learning are still not fully in line with student expectations; Many obstacles were experienced while participating in online learning; Satisfaction with the ability to capture material is still not obtained by students. Interpretation: In online learning during this pandemi, students have not been satisfied with the expected quality of learning. Implications: carrying out online learning with methods that are adapted to the needs and expectations of students by going through a process of assessing student needs first, in order able to evenly adjust the abilities and characteristics of students able to get maximum quality learning.